Ideae magnanimitatis Illyricae et Pannonicae: héroïsme baroque et (dé)construction de la mémoire exemplaire nationale - Blažević, Zrinka (2011)
This paper highlighted an apparently anachronistic phenomenon of the construction of the early modern "Illyrian" national memory on the example of the almost forgotten poem Ideae magnanimitatis Illyricae et Pannonicae (Ideas of the Illyrian and Pannonian magnanimity, Zageb, 1705) written by Ivan Franjo Čikulin. Since the poem was primarily aimed at educating the youth of the Jesuit academy in Zagreb, this paper primarily analysed the rhetorical and poetical strategies and modalities of interorization of the normative and legitimate national memory in the discourse of the baroque heroism (e.g. genological translation, exemplary inscenation of virtus heroica etc.). Judging from the structural features of the poem, it seems that the discursive construction and representation of the Illyrian and Pannonian national memories are founded upon the principle of parallelism and equivalency, but a close reading revealed the popular baroque strategy of contrastive dissimulation, by which ethically superior Illyrian national autostereotype was built as a contrast to the negative or, at least, ethically ambivalent "Pannonian" heterostereotype. At last, the historical and political contextualisation disclosed a main pragmatic function of the Čikulin's poem which served as a dispository pedagogical model of ethical and political formation for the Croatian youth according to the actual emancipatory politics of the Croatian Estates.
Projekt MZOS
Projekt MZOS
FRA